How Big is the Tax Advantage to Debt? - Kane, Alex; Marcus, Alan J.; McDonald, Robert L. (Journal of Finance, 1984)
This paper uses an option valuation model of the firm to answer the question, "What magnitude tax advantage to debt s consistent with the range of observed corporate debt ratios?"We incorporate into the model differential personal tax rates on capital gains and ordinary income.We conclude that variations in the magnitude of bankruptcy costs across firms can not by itself account for the simultaneous existence of levered and unlevered firms.When it is possible for the value of the underlying assets to junip discretely to zero, differences across firms in the probability of this jump can account for the simultaneous existence of levered and unlevered firms.Moreover, if the tax advantage to debt is small, the annual rate of return advantage offered by optimal leverage may be so small as to make the firm indifferent about debt policy over a wide range of debt-to-firm value ratios.